Explain the role of the mosque in the cohesion of the physical-spatial structure of the neighborhood - Vahid Sarafraz; Reza Kheyredin; Mehran Alalhesabi (هنر اسلامی, 2022)
In terms of the nature and type of study, it is a concept; in terms of the study method, it is descriptive-analytical. "Social solidarity" and "physical-spatial cohesion" are two interrelated concepts. It seems that one of the reasons for the decrease in this relationship should be sought in the lack of coordination and balance between the two. On the other hand, in Islamic cities, monotheism is one of the principles of Sharia in Islam. has brought. Thus, recognizing and manifesting the principles governing societies will be an operational strategy for the cohesion and integrity of the environment. The results showed that among the indicators that make the mosque as a cohesive element in the city are unity, unity of the nation and the behavior of the mosque as the most important criteria for the decisive role of the mosque. Also, the mosque and its impact on its surrounding area, in the chaotic and unfavorable conditions of the urban structure, is a quick-return strategy on a micro and metropolitan scale. The design of the mosque in a way that meets the requirements of its time will turn the worldview in the living space into objectivity. In addition to meeting the material and spiritual needs in the living space, the mosque has always been unifying and an indicator of the identity of Islamic-Iranian neighborhoods.